외국어로서의 한일 자국어 교육정책 비교 연구 : 법제화 과정을 중심으로 - 류경희 (Foreign Languages Education, 30(4), 2023)
This paper compares the language policies implemented in Korea and Japan based on the Korean Language Basic Law and the Promotion of Japanese Language Education Act. The research examines the purpose, background, key policy agencies, measures taken, and achievements of legislation in order to gain insight into the philosophy behind and direction of national language education as a foreign language. The findings are summarized as follows: Firstly, there are differences between Korea and Japan in terms of the process and background of enacting policies for native language education as a foreign language. But in both cases, the legislation regarding language policies carries significant meaning as it imposes obligations on responsible bodies. Secondly, there are points worth noting regarding the content aspect that constitutes educational curricula. Within educational curricula frameworks lie ideological values inherent within them. Both Korean and Japanese languages’ educational curricula as foreign languages fundamentally embrace multilingualism and interculturalism.